ANALYSIS OF COMMUNITY EDUCATION ON PARTICIPATION IN THE MEDAN CITY DEVELOPMENT PROGRAM - Vera Asihna Riris Pasaribu (The American Journal of Interdisciplinary Innovations and Research, 2024)
Research purposes As for goals from study This is For now and analyze variable extent role Government, level poverty , as well provision field Work influential to participation in development of Medan City through HR development as intervening variables . Originality Subject from study This is residents / people of Medan City, where variables in the research This is variable independent, that is role Government , level poverty , as well provision field work , variable dependent , i.e variable participation in development of Medan City as well as intervening variables are variable HR development . The results of the data analysis used use SEM analysis with using SMART PLS 4.0 software. Data collection techniques through studies observation and questionnaires. Design/ methodology / approach Method study with use method descriptive quantitative data analysis using method structural equation model (SEM), where results process data with SEM method was carried out with PLS 4.0 application . Findings From results study the so the existing conclusion , namely in a way Partial variable role Government , level poverty and provision field Work influential to participation in development and influence to HR development . By simultaneous variable role Government , level poverty and provision field Work influential to participation in development through variable HR development as intervening variable . Implementation The more real role Government in enhancement provision education to society , then will increase HR development is increasing real and will be make participation public in development will Keep going contribute in enhancement results development . The more increase level poverty and reduction field work , then will lower existing and future HR capabilities hinder to contribution real society within development .